ANALISIS PANJANG ANTRIAN DAMPAK REKAYASA LALU LINTAS CIPAGANTI MENGGUNAKAN SIMEVENTS MATLAB - Chaeruddin, Sultan; Fajar, Yusuf; Harahap, Erwin (KITA Institut, 2020)
Car and motorcycle vehicles are vital needs in this modern era to help someone to a certain place. Inevitably the increasing number of cars and motorbikes with fewer roads to accommodate these vehicles results in congestion or long queues that are so crowded. So the government also conducted several methods to unravel congestion, including traffic engineering. This method can be said to be successful if congestion in an area can decrease from usual. However, not every successful traffic engineering, even congestion is getting worse. Therefore we need to test the results of traffic engineering. One of them is using the M/M/1 queuing model with Poisson distribution and then simulated by SimEvents in Matlab. As researchers, we can also provide solutions to unravel these bottlenecks. The traffic engineering that we are going to analyze is Cipaganti traffic engineering, Bandung. Keywords:queue; traffic engineering; SimEvents; cipaganti.